The Effect Of Accounting Conservatism On Earnings Quality With Ownership Structure As A Moderating Variable - Lukman Tuwo; Fransiskus Randa; Itnoy Caesar Sudewa (Contemporary Journal on Business and Accounting, 2026)
Purpose – This study investigates the effect of accounting conservatism on improving earnings quality, moderated by ownership structure. Agency theory and signaling theory are used to explain the relationship between the variables. Design/methodology/approach – The study population consisted of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Secondary data sources included financial statements and annual reports obtained from the Indonesia Stock Exchange and the companies' official websites. A sample of 97 companies spanning three years was selected using a purposive sampling method. Findings – The results indicate that accounting conservatism has a positive and significant effect on earnings quality, institutional ownership has a positive and significant effect on earnings quality, and managerial ownership has a negative and significant effect on earnings quality. Originality – This study also indicate that institutional ownership does not moderate the relationship between accounting conservatism and earnings quality. Finally, the study found that managerial ownership moderates the relationship between accounting conservatism and earnings quality.